2019
DOI: 10.1016/j.addbeh.2018.10.011
|View full text |Cite|
|
Sign up to set email alerts
|

Smoking and quitting behaviours by mental health conditions in Great Britain (1993–2014)

Abstract: Smoking is a major contributor to the disparity in life expectancy between those with and without a mental health condition. Previous work has found associations between individual conditions such as depression and current smoking, cigarette consumption and dependence, but did not compare a range of specific mental disorders. Using data from the nationally-representative Adult Psychiatric Morbidity Survey, we characterised trends in smoking prevalence in the general population in Great Britain and among those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 34 publications
10
82
0
1
Order By: Relevance
“…Both a US survey (12,28) and the present survey found that those with psychological distress were more likely to have made at least one quit attempt in the past year. The present finding that those with a mental health problem are at least as likely to be motivated to stop smoking is in line with earlier findings which used different measures to measure related constructs (4,28,35). Previous research from the US found that current cigarette smokers with mental health problems were not statistically more likely to be using electronic cigarettes, this is in contrast to the present findings (36,37).…”
Section: Quit Attemptssupporting
confidence: 90%
See 1 more Smart Citation
“…Both a US survey (12,28) and the present survey found that those with psychological distress were more likely to have made at least one quit attempt in the past year. The present finding that those with a mental health problem are at least as likely to be motivated to stop smoking is in line with earlier findings which used different measures to measure related constructs (4,28,35). Previous research from the US found that current cigarette smokers with mental health problems were not statistically more likely to be using electronic cigarettes, this is in contrast to the present findings (36,37).…”
Section: Quit Attemptssupporting
confidence: 90%
“…Tobacco control strategies have led to an overall decline in smoking prevalence in countries such as the UK and US, however, there remains a large gap in smoking prevalence between people with and without mental health problems. Among those with a common mental health disorder in England, smoking prevalence remains around 50% higher (4) and this increases further for more severe mental disorders (5). Figures for the US similarly show an increased burden of smoking among those with 3 mental health problems (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Reporting alcohol problems was only found to be negatively associated with being abstinent, consistent with other studies 2,14 . Depression and anxiety were the two most commonly reported problems, and those reporting them were more likely to report recent (failed) attempts, consistent with existing research 28 , but had significantly lower self-efficacy, suggesting difficulties and challenges they faced to quit smoking 2,17,18 . It is also worth noting that daily smokers with these two mental conditions were more likely to use quit medications on their last quit attempts, while such positive associations were not found for other groups of conditions except for chronic pain.…”
supporting
confidence: 77%
“…Smoking rates have declined in the general population over the last few decades but not among people with indicators of longstanding mental disorders or recent psychoactive medication usage 17 . A recent study in the UK found equivocal evidence, but the gap in smoking between the general population and those with mental disorders is not closing 18 . Depression, especially severe depression, seems to make it difficult for smokers to quit even though they are aware of the long-term harms of smoking 2,19,20 .…”
Section: Introductionmentioning
confidence: 98%
“…3 Although new figures suggest that this prevalence is starting to decline, smoking rates among people with common mental health conditions remain around 50% higher than those in the wider population. 4,5 However, the effects of smoking go far beyond reduced life expectancy; it influences employment prospects, 6 reduces earnings, 6 increases care needs 7 and causes poverty. 8 Higher smoking rates are associated with every indicator of disadvantage, but most adult smokers want to quit.…”
Section: The Challengementioning
confidence: 99%